Stock return outliers and beta estimation: The case of U.S. pharmaceutical companies - Theodossiou, Alexandra K.; Theodossiou, Panayiotis (My University, 2014)
Efficient estimation of the equity cost of operating public corporations is essential for a rational investment policy. Traditional OLS beta estimates of a single stock are known to suffer from violations of normality due to outliers - extreme returns caused by large, unpredictable company-specific events. We confirm the presence of an outliers-driven, often significant bias in OLS beta estimates by undertaking parallel estimates with a related method based on a mixed-return model that follows Huber's Robust M (HRM) estimator. We demonstrate that the OLS bias can be substantial even in a sample spanning 18 years of monthly observations.
Keywords: Equity cost of capital; OLS estimation; Pharmaceutical industry; Robust M estimation; Stock beta